Relationship of Child Perceptions of Maternal Pain to Children’s Laboratory and Nonlaboratory Pain - Subhadra Evans; Jennie CI Tsao; Lonnie K Zeltzer (Pain Research and Management)
Previous research has established links between parent and child pain. However, little is known about sex-specific parent-child pain relationships in a nonclinical population. A sample of 186 children aged eight to 18 years (49% female) provided information on maternal and self bodily pain, assessed by asking children about the presence and location of bodily pain experienced. Children also completed three laboratory pain tasks and reported on cold pressor pain intensity, pressure pain intensity and heat pain intensity. The presence of child-reported maternal pain was consistently correlated with daughters’ bodily and laboratory pain, but not with sons’ pain in bivariate analyses. Multivariate analyses controlling for child age and maternal psychological distress indicated that children of mothers with bodily pain reported more total bodily pain sites as well as greater pressure and cold pain intensity, relative to children of mothers without bodily pain. For cold pain intensity, these results differed for boys versus girls, in that daughters reporting maternal pain evidenced significantly higher cold pain intensity compared with daughters not reporting maternal pain. No such differences were found for boys. The findings suggest that children’s perceptions of maternal pain may play a role in influencing children’s own experience of pain, and that maternal pain models may affect boys and girls differently.